Struktur dan Modalitas dalam Tajuk Rencana Media Indonesia Berjudul “Menunggu PDIP Jadi Oposisi” - Lathifah Nur Annisa; Hendra Setiawan (PRASASTI: Journal of Linguistics, 2025)
This research analyzes an editorial from Media Indonesia entitled "Waiting for PDIP to Become Opposition," with a focus on the structure of the news and the language modalities used. The aim is to understand how the use of language and sentence structure in editorials can influence readers' perceptions of the political issues discussed. The method used is descriptive qualitative with reading and note-taking analysis techniques. Data was obtained from the online media portal Media Indonesia, with an editorial published on April 29 2024. Data analysis involved several stages, including condensing, displaying, drawing conclusions and verifying. Data are presented informally. The research results show that the editorial structure is in accordance with an inverted pyramid, including the news title, news core, news content, and end of the news. In addition, there are 11 modality data which can be grouped into three types: intentional modality, epistemic modality, and deontic modality. This research makes an important contribution in understanding how news structure and the use of language modalities influence readers' perceptions of political issues. By analyzing the editorial "Waiting for PDIP to Become Opposition" from Media Indonesia, the methodology used has proven effective in exploring key aspects of news texts. By finding that the editorial structure adheres to an inverted pyramid and the existence of modalities that include intentional, epistemic, and dynamic modalities, this research provides valuable insights for further understanding of how the media shapes and influences public opinion regarding politics.